Simulation and System Design of a 3D Metrology Optical System Based on a Bidirectional OLED Microdisplay - Constanze Großmann; Ute Gawronski; Martin Breibarth; Gunther Notni; Andreas Tünnermann (Advances in Materials Science and Engineering)
Innovative display technologies enable a wide range of different system applications. specifically, in metrology, medical, and automotive applications microdisplays were increasingly used. In the last decades OLED microdisplays were in the focus of display development. A new class of OLED microdisplays with an integrated photodiode array is the latest development. The so-called bi-directional OLED microdisplays combine light-emitting devices (AM-OLED microdisplay) and photo sensitive detectors (photodiode matrix) on one single chip based on OLED-on-CMOS-technology. Currently this kind of display is still a prototype. Based on such a novel bidirectional OLED microdisplay, we present for the first time a system simulation and design of a 3D optical surface metrology system. The first step is the full characterization of the microdisplay. Depending on the characterization results the future system parameters are determined. Based on the characterization results and the application parameters the system design parameters are defined. The functionality of the system is simulated, and a theoretical proof of concept is presented. An example for our application on 3D optical surface metrology system is evaluated.